Optimal hematocrit for maximal exercise performance in acute and chronic erythropoietin-treated mice - Schuler, B.; Arras, M.; Keller, S.; Rettich, A.; Lundby, C.; Vogel, J.; Gassmann, M. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Erythropoietin (Epo) treatment increases hematocrit (Htc) and, consequently, arterial O2 content. This in turn improves exercise performance. However, because elevated blood viscosity associated with increasing Htc levels may limit cardiac performance, it was suggested that the highest attainable Htc may not necessarily be associated with the highest attainable exercise capacity. To test the proposed hypothesis that an optimal Htc in acute and chronic Epo-treated mice exists—i.e., the Htc that facilitates the greatest O2 flux during maximal exercise—Htc levels of wild-type mice were acutely elevated by administering novel erythropoiesis-stimulating protein (NESP; wtNESP). Furthermore, in the transgenic mouse line tg6 that reaches Htc levels of up to 0.9 because of constitutive overexpression of human Epo, the Htc was gradually reduced by application of the hemolysis-inducing compound phenylhydrazine (PHZ; tg6PHZ). Maximal cardiovascular performance was measured by using telemetry in all exercising mice. Highest maximal O2 uptake Graphic and maximal time to exhaustion at submaximal exercise intensities were reached at Htc values of 0.58 and 0.57 for wtNESP, and 0.68 and 0.66 for tg6PHZ, respectively. Rate pressure product, and thus also maximal working capacity of the heart, increased with elevated Htc values. Blood viscosity correlated with Graphic Apart from the confirmation of the Htc hypothesis, we conclude that tg6PHZ adapted better to varying Htc values than wtNESP because of the higher optimal Htc of tg6PHZ compared to wtNESP. Of note, blood viscosity plays a critical role in limiting exercise capacity.